Controlling Bloat in Genetic Programming for Sloving Wall Following Problem - Navid Bazrkar; Mostafa Nemati; Reza Salimi (IAES International Journal of Robotics and Automation (IJRA), 2014)
The goal in automatic programming is to get a computer to perform a task by telling it what needs to be done, rather than by explicitly programming it.With considers the task of automatically generating a computer program to enable an autonomous mobile robot to perform the task of following the wall of an irregular shaped room, During the evolution of solutions using genetic programming (GP) there is generally an increase in average tree size without a corresponding increase in fitness—a phenomenon commonly referred to as bloat. Many different bloat control methods have been proposed. This paper review, evaluate, implementation and comparison of these methods in wall following problem and the most appropriate method for solving bloat problem is proposed.